A Stored Products Pest (no official common name), Oryzaephilus acuminatus (Insecta: Coleoptera: Silvanidae) - Michael C. Thomas; Robert E. Woodruff (EDIS, 2004)
A commercial nursery in Fort Myers, Florida imported seeds of the neem tree (Azadirachta indica A. Juas) from India to be used for their purported insecticidal properties. Beetles were discovered in the storage area on 11 January 1983 and were sent to the Florida Department of Agriculture for identification. They were identified by the senior author as Oryzaephilus acuminatus Halstead, constituting the first United States record. Recommendations were immediately made to fumigate the area where the seed was stored in order to prevent establishment of the pest. This document is EENY-188 (originally published as DPI Entomology Circular 257), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2001.